Impact of geographic origin on access to therapy and therapy outcomes in the Swiss Hepatitis C Cohort Study. - Matteo Brezzi; Barbara Bertisch; Maroussia Roelens; Darius Moradpour; Benedetta Terziroli Beretta-Piccoli; Nasser Semmo; Beat Müllhaupt; David Semela; Francesco Negro; Olivia Keiser; Swiss Hepatitis C Cohort Study (PLoS ONE, 2019)
Late diagnosis and treatment may increase morbidity and mortality among persons with hepatitis C virus (HCV) infection. We included all participants of the Swiss Hepatitis C Cohort Study (SCCS). We used unadjusted and adjusted logistic and Cox regressions to determine the association between the geographic origin of the participants and the following outcomes: antiviral treatment status; sustained virologic response; cirrhosis at enrolment; incident cirrhosis; loss to follow-up (LTFU); and mortality. The analyses were adjusted for sex, baseline age, education, source of income, alcohol consumption, injection drug use (IDU), HCV genotype, HIV or HBV coinfection, duration of HCV infection, time since enrolment, cirrhosis, (type of) HCV treatment, and centre at enrolment. Among 5,356 persons, 1,752 (32.7%) were foreign-born. IDU was more common among Swiss- (64.1%) than foreign-born (36.6%) persons. Cirrhosis at enrolment was more frequent among foreign- than Swiss-born persons, reflecting the high frequency of cirrhosis among Italian-born persons who acquired HCV between 1950 and 1970 in Italian healthcare settings. Although antiviral treatment coverage was similar, the sustained viral response rate was increased and the mortality was lower among foreign-vs. Swiss-born persons, with the lowest mortality in persons from Asia/Oceania. LTFU was more frequent in persons from Germany, Eastern and Southern Europe, and the Americas. In conclusion, in Switzerland, a country with universal healthcare, geographic origin had no influence on hepatitis C treatment access, and the better treatment outcomes among foreign-born persons were likely explained by their lower prevalence of IDU and alcohol consumption than among Swiss-born persons.